SENI RESITASI ROYONG DALAM RITUAL DAUR HIDUP ETNIS MAKASSAR DI KABUPATEN GOWA - Solihing . (SELONDING, 2012)
Royong recital performance art is a song or chanting in an artistic lyric. The ethnic of Makassar believe that the lyric chanted by royong reciting singers represents the prayer for safety and protection to live the life of the one chanted with royong lyric. In the life-cycle ceremony of a wedding, the chanted lyric of royong implies a prayer for happiness and wellbeing. The lyric recited during the life-cycle ritual, especially attompolok and assuna, represents mythical story to incite good fortune, prevent turmoil, and salvation prayer. It is also intended to form a character based on existing norms, for the survival of their children later, and the recitation is in Makassar Turiolo (the anchestors). The story in the royong lyric, according to the people of Makassar, is a myth believed to bring wellbeing for the chanted child, and is praying for the child to grow in a healthy condition until his or her adulthood. Keywords: Royong, Initiation, Makasar people